Pharmaceuticals, physicians and money - Aleksanyan, Yeva, author; Zahran, Sammy, advisor; Mushinski, David, advisor; Pressman, Steven, committee member; Pena, Anita Alves, committee member; Stallones, Lorann, committee member (Colorado State University. Libraries, 2022)
Pharmaceutical companies have contributed tremendously to improving health and quality of life. Treatments unavailable decades ago now extend lives and eliminate the need for invasive medical procedures. New cures are developed every year through research and development. Pharmaceutical companies typically face high failure rates while investing in research and development, the size of which may reach as high as 2.56 billion dollars (Kakkar, 2015). To increase returns from the products that are finally in the market, pharmaceutical companies engage in medical marketing. Medical marketing, and particularly promotions to physicians, come with a hefty cost to a final consumer. Numerous studies have found associations between promotional payments and brand name prescribing (Yeh et al., 2016; Perlis and Perlis, 2016), even if equivalent low-priced products are available (Akande and Aderibigbe, 2007; Taylor et al., 2016). This dissertation explores pharmaceutical industry-physician relationships and examines the factors influencing the size and frequency of promotional payments to physicians. The dissertation also studies the behavior of physicians and considers why some physicians accept more in payments than others. Chapter one examines the behavior of pharmaceutical companies, the patterns of competition surrounding patent expiration, the generic entry, and the choice of promotional instruments. It discusses the strategies employed by pharmaceutical companies in their efforts to keep competition away from the market and enjoy longer periods of monopoly or duopoly power. The study argues that patent expiration and subsequent entry of generic competitors are strong predictors of promotional payments. Also, pharmaceutical companies drastically change the size and frequency of payments after FDA approval of new dosages or new uses of an existing drug for the purposes of shifting the market away from the generic competition and increasing revenues. Finally, the chapter discusses the issues surrounding the information and persuasion debate, showing that promotional payments serve both purposes. Chapter two examines the role of cultural norms and the regulatory environment in the acceptance of pharmaceutical promotional payments by foreign-trained internal medicine doctors. It shows that the home country's corruption norms and the host country's regulatory environment are both important predictors of corrupt behavior among foreign-trained physicians. In the absence of rules and regulations, physicians from different countries adopt somewhat similar behavior. However, the propensity to accept promotional payments decreases among physicians from less corrupt countries when a host country's regulatory environment restricts acceptance of such payments. The study also finds a strong relationship between tenure, physician gender, and propensity to accept promotional payments. It suggests considering different norms and cultural backgrounds when designing and integrating ethical training in the residency and fellowship curricula. It also recommends adopting more stringent conflict of interest policies in hospitals. Chapter three analyzes the relationship between medical school policies and the propensity of promotional payment acceptance later in a physician's career. It shows that some medical school policies affect the likelihood and the size of accepted promotional payment and interactions with the pharmaceutical representatives later in a physician's career. Restrictive medical school meal policies seem to be especially effective in reducing interactions and acceptance of food and beverage-related payments. The study also finds a strong relationship between tenure, physician gender, physician practice size, and propensity to accept promotional payments. It suggests adopting stringent medical school policies to influence payment acceptance behavior later in physicians' careers.
Keywords: medical school; pharmaceutical companies; promotional payments; norms; institutions; physicians